Guide to the international registration of marks under the Madrid agreement and the Madrid protocol (WIPO publication, 2016)
This Guide is primarily intended for applicants for, and holders of, international registrations of marks, as well as officials of the competent administrations of the members of the Madrid Union. It covers the various steps of the international registration procedure and explains the essential provisions of the Protocol Relating to the Madrid Agreement Concerning the International Registration of Marks and the Regulations under the Protocol. Esta Guía está destinada principalmente a los solicitantes y titulares de registros internacionales de marcas, así como a los funcionarios de las administraciones competentes de los miembros de la Unión de Madrid. Abarca los diversos pasos del procedimiento de registro internacional y explica las disposiciones esenciales del Protocolo relativo al Arreglo de Madrid relativo al Registro Internacional de Marcas y el Reglamento del Protocolo.